Anti‐microbial resistance of Salmonella isolates from raw meat‐based dog food in Japan - Shoichiro Yukawa; Ikuo Uchida; Hiroshi Takemitsu; Asako Okamoto; Motomi Yukawa; Seinosuke Ohshima; Yutaka Tamura (Veterinary Medicine and Science, 2022)
Abstract Background Salmonella contamination of raw meat‐based diets (RMBDs) for pets poses a major public health concern but has not been investigated in Japan. Objective To investigate Salmonella contamination in RMBDs for dogs marketed in Japan and the anti‐microbial resistance profiles of the Salmonella isolates. Methods Sixty commercial RMBD samples were collected in the Okayama and Osaka Prefectures, Japan, between December 2016 and March 2017. The obtained Salmonella isolates were serotyped, their anti‐microbial resistance patterns were determined, and the anti‐microbial‐resistant isolates were screened for the presence of resistance genes by polymerase chain reaction. Results Salmonella enterica subsp. enterica was detected in seven of the 60 RMBD samples. Among them, five isolates were identified as S. Infantis (n = 3), S. Typhimurium (n = 1) and S. Schwarzengrund (n = 1), while the serotypes of two isolates were unable to be identified. All isolates were susceptible to ampicillin, cefazolin, cefotaxime and gentamycin. Two isolates were resistant to more than one anti‐microbial agent; one of the S. Infantis isolates was resistant to streptomycin, kanamycin, tetracycline and trimethoprim, while the S. Typhimurium isolate was resistant to nalidixic acid, ciprofloxacin and chloramphenicol. The S. Schwarzengrund isolate was resistant to tetracycline. Additionally, the S. Typhimurium isolate harboured the anti‐microbial resistance gene gyrA with a mutation corresponding to Ser‐83→Phe amino acid substitution. Conclusion The study findings suggest that RMBDs for dogs marketed in Japan can be a potential source of Salmonella infection for dogs and humans including infections caused by quinolone‐resistant isolates.